DIFFERENCE BETWEEN INTERNAL AND EXTERNAL SUPPLY CHAIN RISKS ON ITS PERFORMANCE (Singaporean Journal of Business Economics and Management, 2013)
Supply chain management as one of the twenty-first century manufacturing paradigm in improving the competitiveness of the enterprise, is important. Also, increasing competition in global markets and customer expectations have led to more carefully examination supply chains in organizations. Purpose of this study is assessing the impact of the difference between internal supply chain risks and external supply chain risks on supply chain performance. This research in terms of the purpose is the applied and in term of methods and implementation is descriptive from type of survey and a method of collecting data in this research is field. Also research tool is questionnaire. Food Industries companies of Rasht is considered as the statistical population that number of food industries companies in Rasht is 108 units and sample is consists of 84 units. Sampling method is convenience non-probability. Research hypotheses were tested through ANOVA and regression and t-test. The results of testing data show that there is no significant difference between the likelihood of internal and external risks. But external supply chain risks have a greater impact on the supply chain than internal supply chain risks and also the result of ANOVA indicated that there is significant differences between the different levels of the company's risk management with performance. le whatever higher the level, the average corporate performance will be higher.